2014
DOI: 10.1186/s12888-014-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for relapse among Individuals with Schizophrenia: A Qualitative Study in Dar es Salaam, Tanzania

Abstract: BackgroundRelapse in people with schizophrenia is a major challenge for mental health service providers in Tanzania and other countries. Approximately 10% of people with schizophrenia are re-admitted due to relapse at Muhimbili National Hospital (MNH) Psychiatric Unit each month. Relapse brings about negative effects and it results in a huge burden to patients, their families, the mental health sector and the country’s economy. So far no study has been done to address relapse in Tanzania. The purpose of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 40 publications
1
45
3
8
Order By: Relevance
“…We observed a good adherence to treatment plus good family support which provide better outcome and prognosis. This is in agreement with other reports in the literature that have demonstrated that a combination of family support and knowledge of the disease help families and persons with schizophrenia to lessen the relapse frequency and improve compliance with the treatment [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a good adherence to treatment plus good family support which provide better outcome and prognosis. This is in agreement with other reports in the literature that have demonstrated that a combination of family support and knowledge of the disease help families and persons with schizophrenia to lessen the relapse frequency and improve compliance with the treatment [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…No Penulis/negara Metode Kondisi N Nama aplikasi/web Fitur aplikasi/web dan program intervensi 1 Xu D et al (19) Cina Fitur data demografi klien Fitur randomisasi responden berdasarkan data demografi, hasil randomisasi akan dikirimkan via email ke responden Fitur pengisian kuesioner Early Warning Sign (EWS) melalui telepon genggam klien dan keluarga Apabila hasil kuesioner menunjukkan adanya keparahan gejala maka email secara otomatis akan terkirim ke petugas yang merawat Klien dianjurkan mengunjungi pelayanan kesehatan dan akan diberikan tambahan terapi 3 Gottlieb JD et al (21) USA Fitur pengkajian early warning sign pada kekambuhan untuk menilai kekambuhan pada klien yang mendapatkan intervensi 1 tahun pengurangan dosis terapi antipsikotik 9 Kidd SA et al (27) Kanada (31) Cina…”
Section: Tabel 1 Karakteristik Artikel Pencegahan Kekambuhan Klien Sunclassified
“…Kekambuhan disebabkan oleh ketidakpatuhan klien minum obat. (4,8,9) Faktor penyebab lainnya adalah ketidakmampuan mengidentifikasi dan mengontrol tanda dan gejala kambuh. (4) Faktor penyebab kekambuhan yang berasal dari keluarga adalah kurangnya dukungan keluarga, expressed emotion (EE) keluarga yang tinggi, pengetahuan tentang psikosis yang buruk, dan ketidakmampuan keluarga merawat klien skizofrenia.…”
Section: Pengkajian/asesmenunclassified
“…Sariah (2014) menyimpulkan bahwa salah satu penyebab kambuhnya penyakit skizofrenia disebabkan oleh peristiwa kehidupan keluarga yang penuh dengan tekanan (stres).…”
Section: Pembahasanunclassified